First record of the nonindigenous parasitic copepod Neoergasilus japonicus (Harada, 1930) in Turkey - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2012)
Neoergasilus japonicus (Harada, 1930), a parasitic copepod from the family Ergasilidae (Copepoda, Poecilostomatoida), was observed for the first time in Turkey during a parasitological examination of rudd Scardinius erythrophthalmus from Lake Sapanca. The investigation was performed between March 2009 and February 2010, and a total of 132 S. erythrophthalmus were studied at monthly intervals. N. japonicus infection was found from June to November, and during this period the monthly prevalences were 18.2%, 75.0%, 53.8%, 61.5%, 38.5%, and 33.3%, respectively. The average prevalence in female rudd was higher than in males. A total of 467 adult female N. japonicus individuals were collected, and the maximum intensity of infection, 52 specimens of N. japonicus, was found on a single fish in August. The preferred attachment sites of N. japonicus were the anal fin, with 261 individual parasites (55.9%), and the dorsal fin, with 179 (38.3%).
Keywords: Neoergasilus japonicus; parasitic copepod; nonindigenous species; rudd; Lake Sapanca; ERGASILID COPEPODS; POECILOSTOMATOIDA